Critical Reading Material Development based on Quran for Arabic Student - Edy Murdani Z; Wildana Wargadinata; Sutaman Sutaman (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
This study aims to develop critical reading skills material based on conversations in the Koran for Arabic Language Students at IAIN Samarinda. The research method used is the research and development of the Balitho and Jolly models with the following stages: (1) identification of the problem as a disclosure of needs; (2) exploration as a needs analysis; (3) realization of context as product design planning; (4) pedagogical realization as product preparation; (5) Product realization as the initial product and validation of the expert team; (6) implementation as a product test in the field in limited groups and large groups; (7) evaluation as a revision for product improvement. The results of the study: (1) the teaching material for critical reading skills based on conversations in the Koran (2) The teaching material has characteristics (a) contains facts and opinions; (b) the material contains many arguments; (c) contains many words which, if expressed correctly, can create new understandings (3) the application of teaching materials to Arabic students shows quite effective results. The new finding of this research is the teaching material which contains various facts and opinions, as well as many arguments that can improve students' ability to think critically.